Peningkatan kapasitas masyarakat dalam menumbuhkan literasi lingkungan untuk mewujudkan kesadaran konservasi sumber daya air di wilayah kawasan hutan Desa Cihaur - Prasetio, Pajar Anugrah; Nugraha, Febby Fajar (Abdimas Siliwangi, 2024)
Environmental problems, especially in the Cihaur village forest area, are increasingly complex due to deforestation, pollution and unsustainable use. Forest areas have an important role in maintaining the hydrological cycle and water quality, so that damage to these areas can have a direct impact on the availability and quality of water resources. For this reason, community awareness is needed in active participation to be involved in conservation activities as part of community environmental literacy. The aim of this activity is to strengthen knowledge, awareness, participation and also form partnerships in sensitivity to environmental damage. The method of this activity is through problem analysis, determining the target of the activity, preparing activity materials, determining the time of the activity and carrying out FGD activities to increase community capacity in environmental literacy, especially in water resource conservation activities in forming Water Conservation Concern (KKA). As a result of this activity, the community has awareness which is shown in active participation in a series of KKA activities and the community can analyze environmental problems early and carry out ongoing involvement. The conclusion from this activity is that the Cihaur Village Forest Management Area has the potential to be used as a Water Absorption area if the community cares about preserving this potential based on the existing potential and the need for conservation efforts implemented by the community so that it becomes a sustainable water resource area. Community empowerment is an important factor in mobilizing existing potential in order to improve the quality of resources and maintain the sustainability of their function. The need for collaboration with partners to establish sustainable cooperation while maintaining and growing public awareness as well as community involvement in conservative actions as part of community literacy skills